Alarin but not its alternative-splicing form, GALP (Galanin-like peptide) has antimicrobial activity - Wada, Akihiro; Wong, Pooi Fong; Hojo, Hironobu; Hasegawa, Makoto; Ichinose, Akitoyo; Llanes, Rafael; Kubo, Yoshinao; Senba, Masachika; Ichinose, Yoshio (Elsevier, 2013)
Alarin is an alternative-splicing form of GALP (galanin-like peptide). It shares only 5 conserved amino acids at the N-terminal region with GALP which is involved in a diverse range of normal brain functions. This study seeks to investigate whether alarin has additional functions due to its differences from GALP. Here, we have shown using a radial diffusion assay that alarin but not GALP inhibited the growth of Escherichia coli (strain ML-35). The conserved N-terminal region, however, remained essential for the antimicrobial activity of alarin as truncated peptides showed reduced killing effect. Moreover, alarin inhibited the growth of E. coli in a similar potency as human cathelicidin LL-37, a well-studied antimicrobial peptide. Electron microscopy further showed that alarin induced bacterial membrane blebbing but unlike LL-37, it did not cause hemolysis of erythrocytes. In addition, alarin is only active against the gram-negative bacteria, E. coli but not the gram-positive bacteria, Staphylococcus aureus. Thus, these data suggest that alarin has potentials as an antimicrobial and should be considered for the development in human therapeutics. (c) 2013 Elsevier Inc. All rights reserved.